The current state of knowledge on the role of NKG2D ligands in multiple sclerosis and other autoimmune diseases - Pogoda-Wesołowska, Aleksandra; Sługocka, Nina; Synowiec, Agnieszka; Brodaczewska, Klaudia; Mejer-Zahorowski, Marcin; Ziękiewicz, Maciej; Szypowski, Wojciech; Szymański, Piotr; Stępień, Adam (Frontiers in Molecular Neuroscience, 2025)
Multiple sclerosis (MS) is a chronic central nervous system (CNS) disease with demyelinating inflammatory characteristics. It is the most common nontraumatic and disabling disease affecting young adults. The incidence and prevalence of MS have been increasing. However, its exact cause remains unclear. The main tests used to support the diagnosis are magnetic resonance imaging (MRI) examination and cerebrospinal fluid (CSF) analysis. Nonetheless, to date, no sensitive or specific marker has been identified for the detection of the disease at its initial stage. In recent years, researchers have focused on the fact that the number of natural killer cell group 2 member D (NKG2D) family of C-type lectin-like receptor + (NKG2D+) T cells in the peripheral blood, CSF, and brain tissue has been shown to be higher in patients with MS than in controls. The activating receptor belonging to the NKG2D is stimulated by specific ligands: in humans these are major histocompatibility complex (MHC) class I polypeptide–related sequence A (MICA) and MHC class I polypeptide-related sequence B (MICB) proteins and UL16 binding 1–6 proteins (ULBP1-6). Under physiological conditions, the aforementioned ligands are expressed at low or undetectable levels but can be induced in response to stress factors. NKG2D ligands (NKG2DLs) are involved in epigenetic regulation of their expression. To date, studies in cell cultures, animal models, and brain tissues have revealed elevated expression of MICA/B, ULPB4, and its mouse homolog murine UL16 binding protein-like transcript (MULT1), in oligodendrocytes and astrocytes from patients with MS. Furthermore, soluble forms of NKG2DLs were elevated in the plasma and CSF of patients with MS compared to controls. In this review, we aim to describe the role of NKG2D and NKG2DLs, and their interactions in the pathogenesis of MS, as well as in other autoimmune diseases such as rheumatoid arthritis (RA), inflammatory bowel disease (IBD), systemic lupus erythematosus (SLE), and celiac disease (CeD). We also assess the potential of these proteins as diagnostic markers and consider future perspectives for targeting NKG2D ligands and their pathways as therapeutic targets in MS.